Adobe Flash CS3 Professional - Perkins, Todd. (Berkeley : Lynda.com ; Peachpit Press, 2008)
Provides more than one hundred tutorials on creating Flash animations and interactive files.
"Includes exercise files and demo movies."
Includes index.
System requirements: Windows XP or Vista ; Mac OS X 10.4.8 ; QuickTime 7.0 or later required to view demo movies.
Keywords: Flash (Computer file); Computer animation -- Computer programs; Computer graphics -- Computer programs; Digital video -- Editing -- Data processing; Web sites -- Design